Proposal and simulated characteristics of high-extinction-ratio electroabsorption modulator based on multimode interference waveguide. (27th March 2019) - Yamashina, Kohei; Arakawa, Taro
Abstract: We proposed an electroabsorption modulator (EAM) based on a 1 × 1 multimode interference waveguide (MMI-EAM). A partial electroabsorption (EA) region is asymmetrically placed in a MMI. In a multiple quantum well core layer of the region, the electrorefractive index change is also exhibited in addition to the EA effect, which leads to change in the position of a self-image at the output port of the MMI waveguide. Owing to the combination of the EA effect and change in electrorefractive index, the extinction ratio is significantly improved compared with a conventional EAM with almost the same area of the EA region. We discuss the optimization of the MMI-EAM structure and investigate its modulation characteristics theoretically using the beam propagation method. The results show that the extinction ratio can be increased by 25 dB in the MMI-EAM with the length of 152  μ m and the width of 6  μ m.